Lattice Strain Enhances Thermoelectric Properties in Sb2Te3/Te Heterostructure. (12th November 2019) - Wu, Zhenhua; Chen, Xiang; Mu, Erzhen; Liu, Yang; Che, Zhanxun; Dun, Chaochao; Sun, Fangyuan; Wang, Xinwei; Zhang, Yanliang; Hu, Zhiyu
Abstract: An efficient way to improve thermoelectric (TE) performance of a system by adjusting the lattice strain (e.g., dislocation and nano‐interface) without changing its composition is reported in this study. By controlling the crystallization and growth of Te nanoparticles, a Sb2 Te3 /Te heterostructure with enhanced TE properties is obtained. The growth of Te nanoparticles as well as the introduced lattice strain is characterized by X‐ray diffraction, Raman, and high‐resolution transmission electron microscopy in details. In addition to the low thermal conductivity (κ ) caused by lattice strain, the resulting stress on the heterostructure may lead to a state near electronic topological transition that enhances the power factor ( PF ). As a result, the optimized figure‐of‐merit of the Sb2 Te3 /Te heterojunction reaches up to 0.61 at 300 K with PF and κ of 11.2 µW cm −1 K −2 and 0.55 W m −1 K −1, respectively. This method can also be applied in other heterojunction systems to improve TE properties. Abstract : By controlling the crystallization and growth of Te nanoparticles, a Sb2 Te3 /Te heterostructure with enhanced TE properties is obtained. The crystallization and growth of Te nanoparticles induce lattice strain on the heterostructure to suppress thermal conductivity. In addition, a possible state near ETT may also enhance the thermoelectric properties.